A Contribution to the Study on Sanguo Yanyi: Its Political Standpoint, Character Evaluation, and Character Development. Issue 1 (31st May 2017) - Leijia, Wu
Abstract : This is a study of the Sanguo yanyi (hereafter Yanyi ), one of the four great literary classics of China, in terms of its political standpoint, character evaluation, and character development. It questions the traditional views related to Yanyi's stance of revering Liu Bei 劉備 and belittling Cao Cao 曹操. The argument here is that the novel's political standpoint is mainly based on zhongyi 忠義 (loyalty and righteousness), rather than lineage, benevolence, and other factors. Although Yanyi has a clear political position, it is relatively objective and neutral in evaluating historical figures from different camps. The character development of Yanyi is very successful. The character images are round and rich, rather than flat and stereotypical. Both positive and negative characters have their merits and weaknesses.